2016
DOI: 10.1155/2016/9637173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Features of Medullary Thyroid Carcinoma: The Experience of a Single Center in Costa Rica

Abstract: Background. Activating mutations in the RET gene leads to medullary thyroid carcinoma (MTC). Guidelines encourage performing RET analysis in subjects with hereditary and sporadic disease. Materials and Methods. Design. Observational, case series report study. Patients. Subjects diagnosed with MTC, with a thyroidectomy performed in a single center in Costa Rica between the years 2006 and 2015. Diagnosis and Follow-Up. Pre- and postoperative calcitonin, RET mutation, and neck ultrasound and tomography were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…According to the Surveillance, Epidemiology and End Result (SEER) data report, it has been observed that over the last three decades there is a decreased incidence of MTCs (from 3 to 5% to 1-2%) due to progressive increased incidence of PTCs [1]. The incidence of MTCs at our institution remains at 3-5% as has been previously reported [5][6][7][8]. A referral bias to a quaternary care institution may account for the higher incidence of MTC seen in our series.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to the Surveillance, Epidemiology and End Result (SEER) data report, it has been observed that over the last three decades there is a decreased incidence of MTCs (from 3 to 5% to 1-2%) due to progressive increased incidence of PTCs [1]. The incidence of MTCs at our institution remains at 3-5% as has been previously reported [5][6][7][8]. A referral bias to a quaternary care institution may account for the higher incidence of MTC seen in our series.…”
Section: Discussionsupporting
confidence: 73%
“…A referral bias to a quaternary care institution may account for the higher incidence of MTC seen in our series. The mean age at diagnosis was 40 years as compared to 43-52 years in other reports and there was no female preponderance as was reported in other studies [6,[9][10][11][12][13]. Majority (66%) of patients at presentation had lateral cervical lymph node metastasis demonstrating the aggressive nature of the disease.…”
Section: Discussionmentioning
confidence: 45%
“…Population study for MTC with genotypephenotype correlations in Macedonian patients was performed by Jovanovic et al showing low representation of familiar MTC and MEN2 syndrome in our population, leading to conclusion that those findings may be as a result of absence of appropriate molecular screening and diagnostic algorithm. [17][18][19][20] A population study from RARECARE project, based on the European cancer registries evaluated the frequency of all endocrine malignancies, including from Southeast Europe only Poland and Slovenia. According to this analysis, TCs were represented with 88% of all endocrine malignancies, but this percent was probably higher, since in this project MTC and mixed medullary-papillary and medullary-follicular carcinomas were not included in TC group, and reported average yearly incidence rate of TC was 4/100 000 with significant differences in gender distribution 2.8/1 f/m ratio.…”
Section: Discussionmentioning
confidence: 99%
“…26 In comparison with the regional data, North Macedonia has a very low incidence rate, with f/m ratio similar to that found in the literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our low incidence and prevalence rates may be due to 2 possible reasons, 1: insufficient diagnostics, probably due to low aggressiveness, and indolent course of the disease, thus the cases remain unrecognized and second: the possibility of a low real incidence due to specific etiopathogenetic influences.…”
Section: Discussionmentioning
confidence: 99%
“…The sporadic form of the disease is seen in approximately 75% of all cases. The remaining MTC cases develop as a hereditary disease, occurring as a part of type 2 multiple endocrine neoplasia (MEN2) syndrome (2). MEN 2A constitutes 95% of all MEN 2 cases (3).…”
Section: Introductionmentioning
confidence: 99%